TPROXY dan FILTERING SEBAGAI METODE OPTIMASI PEMAKAIAN BANDWIDTH INTERNET - Sutiyo Sutiyo (Telematika, 2011)
Until now the use of the internet disuatu agencies viewed from the initial planning, use and care, even long-term planning is still not optimal. The main factor lies in the existing human resources, especially in IT personnel and policy makers who do not understand or do not even know at all how your use of the Internet well, optimal, efficient, particularly associated with the consumption of Internet bandwidth. Internet bandwidth capacity greatly affect the speed of web access or other Internet applications. So we need a plan and maintance necessary to obtain good Internet bandwidth consumption efficiency and guaranteed QoS, such as by utilizing Tproxy and filtering methods. TProxy is a development of which has been patched Squid, a proxy to be able to pass traffic without NAT (Network Access Translation). Fitering a firewall system which is used for filtering data packets that do not want filtered dikendaki or akhirmya able to minimize traffic on bandwidth usage. Tproxy and filtering runs on the Linux platform. Linux distributions are often used to Tproxy is a variant Debian, Centos and then to use Mikrotik Filtering. At the end of each request or query from the client or the response of the proxy server does not have meaningful constraints, the bandwidth between the client and the proxy server does not happen limitation, bandwidth capable of running close to capacity including 10 Mbps Ethernet, 100 Mbps, and even a GPS (full speed).